The Effect of Liquidity, Bank Capital, Profitability, and Operational Efficiency On Credit Risk (A Case Study On Banking Sub-Sector Companies Listed On The Indonesia Stock Exchange For The Period 2019-2023) - I Kadek Gita Permana; Henny Rahyuda (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Banks serve as intermediary institutions that collect funds and channel them back into various forms of investment within society. A bank's primary activity of lending funds to the public carries the risk of default or nonpayment by borrowers, referred to as credit risk. Proper management of credit risk is crucial, as increasing proportions of non-performing loans can lead to poor banking health conditions. This study aims to examine, analyze, and explain the influence of liquidity, bank capital, profitability, and operational efficiency on credit risk. The sample for this research consists of 31 banking sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Data were collected using a non-participant observation method. The data analysis technique employed is multiple linear regression analysis, conducted using IBM SPSS version 25 software. The results of the analysis indicate that profitability has a significant negative effect on credit risk, while operational efficiency has a significant positive effect on credit risk. The practical implications of this study provide valuable insights for bank management to maintain profitability levels and operational efficiency to minimize potential credit risks.